PENGARUH INTERAKSI GENOTIP DAN LINGKUNGAN TERHADAP PENINGKATAN PRODUKTIVITAS TANAMAN BAWANG MERAH MENGGUNAKAN METODE SEM-AMMI - Raihanah, Ghina Rizqa; Junaidi, Junaidi; Fadjryani, Fadjryani (PATTIMURA UNIVERSITY, 2021)
Stable and adaptive superior varieties play an important role in increasing plant productivity. The technological innovation was carried out by studying the yield GEI. However, if only paying attention to yield GEI would not be enough in selecting stable and adaptive varieties, so this research used a combination of AMMI and SEM methods. Through the SEM-AMMI, GEI modeling was carried out by taking into account the physiological processes of growth and genotype development which explained the relationship between yield GEI components and how it affected yield GEI. The results of the AMMI biplot showed that genotypes were adaptable and relatively stable were planted in five planting locations, namely Biru Lancor and Tinombo. SEM test results showed that the yield component has an effect on production yield, where the tuber weight above the average will give relatively more onion yields and genotypes planted in relatively low locations, soil pH above 6 and dusty clay soil conditions will produce relatively more red onions and quality.